Effect of intra-articular Platelet Rich Plasma injection on knee Osteoarthritis patients (Northern International Medical College Journal, 2025)
Background: Osteoarthritis (OA) is one of the most common problems that affects human body which may lead to disability. Among the joints of the human body knee joint is most commonly affected by osteoarthritis. Quality of life is greatly affected by OA as it may hamper daily life activities. Several treatment modalities have been adopted to combat the difficulties of knee osteoarthritis. Along with oral medication, lifestyle modification and surgical procedures are also used frequently to treat OA Knee. Sometimes it may be costly and burdensome for patients. Platelet-Rich Plasma (PRP) is a new modality of treatment that is derived from patients' blood containing growth factors that is effective for the_healing process of the damaged articular cartilage and also for tissue regeneration. PRP preparations have been used to treat cartilage lesions to regenerate tissue homeostasis and retard the progression of knee osteoarthritis (OA). The purpose of this study is to determine the effectiveness of intra-articular PRP injections in patients with knee OA and to evaluate clinical outcomes. Methodology: This quasi-experimental study was conducted at the Transfusion Medicine Department in Dhaka Medical College and Hospital. A total of 15 patients who were referred from different departments to Transfusion Medicine for platelet-rich plasma preparation and fulfilled the inclusion criteria were included in this study. Result: Patients received 3 intra-articular PRP injections 21 days apart. Females were predominant 10 (66.66%). Platelet count of the patients was recorded before making PRP and after 1st, 2nd, and 3rd dose of PRP, which was significant by ANOVA test p -value